Influence of maturity condition and habitat type on food resources utilization by Octopus tehuelchus in Atlantic Patagonian coastal ecosystems - Storero, Lorena Pia (2016)
This study evaluates differences in Octopus tehuelchus diet in relation to sex and maturity condition (juvenile, mature, post-spawning) in two contrasting habitat types (sandy vs. rocky). Muscle of O. tehuelchus and of its associated food sources were analyzed for δ13C and δ15N. There was no correlation between δ13C or δ15N and octopus size. δ13C and δ15N values were similar betweensexes indicating similar diets. The Bayesian mixing model (MixSIAR) showed that the proportional contribution of the sources varied with the maturity condition of octopuses, and between habitat types. Our results show differences in the proportions of alternative prey in the diet of O. tehuelchus related to their physiological condition and the habitat characteristics. The differential food source utilization may be related to differential prey energy contribution andcould explain the differences in the growth pattern and life span, as well as in the reproductive traits and recruitment success of O. tehuelchus in sandy and rocky habitats. Our results highlight the importance of considering such differences in octopus diet, since they may have consequences for population dynamics, but also in the species? trophic niche and its functional role in communities.